The Bible in the early Irish church: A.D. 550 to 850 - McNamara, Martin (Commentaria, 2022)
"This book aims at bringing together and providing all the information available on the Bible in the early Irish church (A.D.550-850), drawing on some sources not well known for this subject, such as Columbanus, the early writer Apponius, St Gall list of works in Irish script, and the Libri scottice scripti. The beginnings are stressed after which the biblical compositions for three following centuries are given. The direct links of Irish literal Psalm interpretation with the fourth-century Antioch on the Orontes school are made clear, as is the presence of apocryphal and extra biblical, and possibly Jewish, tradition, in the poems of Blathmac and other Irish compositions"--